Establecimiento de reglas prosociales del tipo aumento formativo (augmenting formative) mediante entrenamiento en discriminaciones condicionales - Pérez Manrique, Tiberio (2022)
The objective of the study was to examine the efficiency of training in formative augmenting pro- social rules. In the experiment six children participated. The intra-subject design proposed by Sidman and Tailby (1982) was used, with two conditions, training and testing. Four phases were applied: establishment of the “self-care” functional class, establishment of the “others” functional class, the establishment of the formative augmenting rule, and test phase. The participants of the experimental phase passed through the four phases of the program, whereas those of the control phase passed through phases 1, 2 and 4. The results demonstrate that the participants who through the experimental phase acquired the formative augmenting rule as product of the training in conditional discriminations based on the sample TO TAKE CARE and its comparers TAX, RAY and JOR with total percentages of relative success of 88,8%, 72,2% and 94,4%, respectively. This data suggests that the establishment of formative augmenting rules is possible by through this type of training